Paruyr Sevak’s novel “Amanej” as a narrative structure - Arzumanyan, Armenuhi (Bulletin of Yerevan University B: Philology, 2025)
In the article titled "Paruyr Sevak’s Novel “Amanej” as a Narrative Structure," we attempted to analyze Sevak’s unfinished novel “Amanej” using the main approaches of narratology, which involves the structural analysis of narrative works. The aim of narratology is to study the structure of narrative works and the artistic functions of the story. The aim of this article is to examine P. Sevak’s unfinished prose work as a completed narrative structure by analyzing the structural layers of the novel according to R. Barthes’ theory. As a result of the research, we reached the following conclusion: By analyzing P. Sevak’s novel “Amanej” using the structural theory of narratology and examining the narrative layers identified by R. Barthes, we observed that P. Sevak’s unfinished novel, with its preserved sections, can be considered a narrative structure with distinct narratological layers. Through the original variations of its ideological system, it achieves a high aesthetic resonance.